Divergent Dynamic Kinetic Resolution of a Racemic Mixture of Four Stereoisomers via N‐Heterocyclic Carbene Organocatalysis. Issue 24 (2nd November 2018) - Vasamsetty, Laxmaiah; Kong, Xiangwen; Meng, Miao; Yang, Shuang; Xu, Weici; Reddy, Pogula Sreekanth; Fang, Xinqiang
Abstract: Racemic mixtures of four stereoisomers are easily formed via many fundamental organic transformations, but the direct utilities of these mixtures have been less studied and remain large challenges to date. In this work, we introduce a new method, i.e., divergent dynamic kinetic resolution, to achieve the separation of racemic mixtures of four stereoisomers. The hypothesis was proved by using a N‐heterocyclic carbene‐catalyzed benzoin reaction, which afforded two separable diastereomeric products bearing three consecutive stereocenters with good to excellent enantioselectivties. We believe that this resolution protocol will find applications in more transformations. Abstract : Providing a good resolution : An N‐heterocyclic carbene‐catalyzed benzoin reaction was employed to achieve the divergent dynamic kinetic resolution of racemic mixtures of four stereoisomers, affording two separable diastereomeric tetralones bearing three consecutive stereocenters with good to excellent enantioselectivties.